Analysis of the Application of the Integrated Catastrophe Risk Model Method for the Flood Insurance Program - Afifah, Nur; Joebaedi, Khafsah; Ismail, Muhammad Iqbal Al-Banna (International Journal of Global Operations Research, 2022)
As the flood rises continue to grow, well-designed insurance programs are becoming an important instrument in flood risk management. One of the obstacles in the flood insurance program is the method used to calculate the premium value. This thesis refers to the Integrated Catastrophe Risk Model (ICRM) which consists of two probability events and stochastic optimization procedures with respect to observation of site-specific risk. The application of the model is illustrated in the study area simulation data. In this thesis, analysis of various aspects of trade-off, new ex-post variables, opportunity occurrence 1 and 2 and minimization of loss function. From the results of research based on these four aspects it can be concluded that the use of Integrated Catastrophe Risk Model method in the optimal flood insurance program.